Lay Pastoral Care : A Narrative Approach - Marshall, Joretta L.; Neuger, Christie Cozad, 1952- (Book collections on Project MUSE., 2022)
Pastoral Care: A Narrative Approach offers guidance for care companions across a spectrum of care. Grounded in narrative theory, Joretta L. Marshall and Christie Cozad Neuger describe practices--based on mutual learning, deepening spiritual growth, and collaborative support--that inform lay care companioning. Curriculum support is included.